2019
DOI: 10.1515/ntrev-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PVA fiber on durability of cementitious composite containing nano-SiO2

Abstract: In the current investigation, the influence of polyvinyl alcohol (PVA) fibers on flowability and durability of cementitious composite containing fly ash and nano-SiO2 was evaluated. PVA fibers were added into the composite at a volume fraction of 0.3%, 0.6%, 0.9%, and 1.2%. The flowability of the fresh cementitious composite was assessed using slump flow. The durability of cementitious composite includes carbonation resistance, permeability resistance, cracking resistance as well as freezing-thawing resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 20 publications
3
32
0
1
Order By: Relevance
“…As shown in Table 1, the specific surface of silica fume is about 43 times larger than that of fly ash in this study. Thus, the super fine silica fume particles could react with Ca(OH)2 very rapidly to produce a large amount of additional C-S-H at early age, densifying the microstructure of concrete and enhancing the mechanical strengths, which is in accordance with previous studies 6,47,48 .…”
Section: Compressive and Splitting Tensile Strengthsupporting
confidence: 90%
“…As shown in Table 1, the specific surface of silica fume is about 43 times larger than that of fly ash in this study. Thus, the super fine silica fume particles could react with Ca(OH)2 very rapidly to produce a large amount of additional C-S-H at early age, densifying the microstructure of concrete and enhancing the mechanical strengths, which is in accordance with previous studies 6,47,48 .…”
Section: Compressive and Splitting Tensile Strengthsupporting
confidence: 90%
“…During the trial, three experimental levels were designed for each parameter, whose values corresponding to the changes in each level are presented in Table 8 below, which were selected based on experience. Among them, the number of neurons was ascertained by the following empirical formula: l = √ n + m + a, a ∈ [1,10], where a is an integer obtained from the boundary of 1-10. The training times were determined according to the convergence times of the trial test.…”
Section: Test Programmentioning
confidence: 99%
“…Concrete is a widely used building material in engineering constructions [1]. With the large-scale construction of long-span bridges, super-high-rise buildings, high-grade highways, large-scale water conservancy facilities, and cross harbor tunnels, concrete materials are endowed with higher expectations [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test results showed that the diatom-FeOx composite exhibited high activity in catalyzing the photodegradation of Rh-6G. Zhang et al [11] evaluated and discussed the effects of nano-SiO 2 on the photocatalytic behavior and durability of cementitious composite incorporated with nano-SiO 2 . The results indicated that the nano-SiO 2 could dramatically improve the photocatalytic performance and durability of cementitious composites.…”
Section: Introductionmentioning
confidence: 99%